Umru’ Al-Qais and His Literary Works: Study of Arabic Writer Thought - Fatoni, Ahmad Sirfi; Umar, Nur Irmayanti (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
This article discusses the life and works of Umru’ al-Qais, a famous Arabic poet from the sixth century. As the son of King Hajar al-Kindi, Umru’ al-Qais was known for his adventurous and extravagant lifestyle, which eventually led to him being banished by his father. After the expulsion, he spent time in the desert until he heard news of his father's death and vowed revenge. His story involves traveling to various regions, including seeking help from the Roman Emperor, who eventually sends a poisoned cloak that causes his death. Umru’ al-Qais was remembered through his works, especially al-Mu'allaqat, which is one of the most famous poems in pre-Islamic Arabic literature. This article also describes his family tree, his influence in Arabic literature, and the style and main themes in his poetry. Umru’ al-Qais recognized as a pioneer in the use of figures of speech and other literary techniques, as well as love poems that describe female beauty and his personal experiences. His poems remain an important reference in the study of Arabic literature